Syntheses of Isoxazoline-Based Amino Acids by Cycloaddition of Nitrile Oxides and Their Conversion into Highly Functionalized Bioactive Amino Acid Derivatives - Kiss, Loránd; Nonn, Melinda; Fülöp, Ferenc (Synthesis, 2012)
The present account illustrates the syntheses of isoxazoline-based amino acids by the cycloaddition of 1,3-dipolar nitrile oxides to the C–C double bond of unsaturated amino acid derivatives, with focus on the regio- and stereoselectivities of the transformations. Emphasis is also placed on the syntheses of highly functionalized amino acids by means of isoxazoline ring opening. The syntheses of various pharmacologically active compounds and their analogues via the above strategies are described. 1 Introduction2 1,3-Dipolar Cycloadditions of Nitrile Oxides3 Syntheses of Isoxazoline-Based Amino Acids3.1 Syntheses of Isoxazoline α-Amino Acids3.2 Syntheses of Isoxazoline γ-Amino Acids and Their Transformation into Bioactive Derivatives3.3 Syntheses of Isoxazoline β-Amino Acids3.3.1 Syntheses of Highly Functionalized Cyclic β-Amino Acids by 1,3-Dipolar Cycloaddition of Nitrile Oxides4 Cycloaddition of Nitrile Oxides to Amino Acid Precursors5 Summary and Outlook
Keywords: amino acids; amino alcohols; cycloaddition; diastereoselectivity; heterocycles; ring opening; stereoselective synthesis